2022
DOI: 10.1093/nutrit/nuab120
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and practical approaches for dietary behavior change in urban socioeconomically disadvantaged adolescents: a systematic review

Abstract: Context There is limited evidence on strategies used to promote dietary behavior changes in socioeconomically disadvantaged urban adolescents and on their effectiveness. Objective A synthesis of nutrition interventions used in this group of adolescents is provided in this systematic review. Data Sources Five electronic databases (PubMed, Web of Science, CINAH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…In contrast to the current study's finding, Poelman et al ( 30 ), in the inquiry among Australian school children, stated that their intervention did not affect behavioral intentions. However, a systematic review by Bel-Serrat et al ( 31 ) identified the importance of targeted behavioral interventions in improving adolescent dietary behaviors. Thus, designing appropriate school-based health promotion and education interventions relying on the assessment of behavioral intention among school students can lead to healthier children fostering regular healthy dietary practices in their homes and communities.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the current study's finding, Poelman et al ( 30 ), in the inquiry among Australian school children, stated that their intervention did not affect behavioral intentions. However, a systematic review by Bel-Serrat et al ( 31 ) identified the importance of targeted behavioral interventions in improving adolescent dietary behaviors. Thus, designing appropriate school-based health promotion and education interventions relying on the assessment of behavioral intention among school students can lead to healthier children fostering regular healthy dietary practices in their homes and communities.…”
Section: Discussionmentioning
confidence: 99%